Analiz dinamiki protsessa povysheniya kvalifikatsii spetsialistov po fizicheshoi kul'turye i sporty - Ageevets, V. U.; Yevseyev, S. P.; Losin, B. E. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
To reveal the effectiveness of the qualification improvement in specialists on physical culture and sport at St.-Petersburg state P.F. Lesgaft academy of physical culture was the purpose of this study. The dynamics of the work at the academy's faculty of qualification improvement in specialists had been studied. The so called "power" of faculty's work had been calculated and its dynamics during 28 years was discussed.